The Influence of Socio-demographic Variables on Coping Strategies for Stress and Depression among Lecturers in Selected Universities of Ogun State, Nigeria - , Oluwaseyi Bewaji; , Osinachi Ekeagwu (Archives of Current Research International, 2024)
Aim: This research investigated the relationship between socio-demographic factors and coping mechanisms for stress and depression among lecturers in selected universities in Ogun State, Nigeria. Sample: A sample population of 285 lecturers from three universities participated in the study. Place and Duration: The study was conducted at three purposively selected universities in Ogun State, Nigeria. Methodology: A total of 285 lecturers participated in the study, representing a response rate of 92%. Data were collected using questionnaires distributed physically and online. Socio-demographic variables such as age, gender, educational level, type of university, academic rank, and years of service were assessed, alongside coping mechanisms for stress and depression. Results: Analysis revealed a diverse range of socio-demographic characteristics within the sample. The study found a moderate utilization of adaptive coping mechanisms for stress and depression, while the prevalence of maladaptive coping strategies remained low. Significant correlations emerged between socio-demographic variables such as age, gender, education level, and academic rank, and both adaptive and maladaptive coping strategies for stress. Additionally, age and gender demonstrated significant associations with coping strategies for depression. Conclusion: These findings underscored the pivotal role of socio-demographic factors in shaping the frequency and nature of coping mechanisms adopted by lecturers. Implications for the design of targeted support interventions within academic environments were discussed. Recommendations: Universities should prioritize implementing policies and training programs that promote adaptive coping mechanisms for stress and depression among lecturers, fostering a supportive environment that enhances their well-being, resilience, and professional effectiveness.